Chronic myeloid leukemia in the Netherlands: a population‐based study on incidence, treatment, and survival in 3585 patients from 1989 to 2012. (30th November 2015) - Thielen, Noortje; Visser, Otto; Ossenkoppele, Gert; Janssen, Jeroen
Abstract: Objective: To assess the impact and results of treatment of CML in the general population, we conducted a population‐based, nationwide study on 3585 CML patients diagnosed between 1989 and 2012 in the Netherlands. Methods: Patient demographics were obtained from the Netherlands Cancer Registry. Information on age, gender, year of diagnosis, first treatment, and date of death were recorded. Overall survival (OS) was adjusted for death rates in the normal population. Results: Incidence in males decreased slightly from 1.2 per 100.000 person years (PY) in 1989–2000 to 0.9 in 2001–2012. For females, incidence remained stable with 0.7 per 100.000 PY in both periods. Incidence was age dependent and highest in males in the last decades of life. Treatment before 2000 mainly consisted of chemotherapy, while after 2007 TKI use was 88%. Five‐year relative survival was only 36% before the introduction of TKIs but significantly increased to 79% after the introduction of TKI. Conclusions: This study gives insight into CML incidence, treatment, and survival in routine care in the Netherlands. Although OS improved since the introduction of TKIs, there is still room for further improvement.